VD_FINDINFO ML / 2011 / 256 vom 9. Juni 2011 - VD Tribunal cantonal (2011)
MAINLEVÉE PROVISOIRE, CAUTIONNEMENT, REPRÉSENTATION, CESSION DE CRÉANCECO, SIGNATURE | 164 al. 1 CO, 165 CO, 20 CO, 2 LReP, 3 LReP, 4 LReP